A descriptive study of the patients with orbital complication of acute and chronic sinusitis - Pullarat, Ahamed Nauphal; C. K., Mohamed Faisal; Nampoothiri, Muraleedhran P.; R., Suma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: This is a descriptive study of all of the patients with orbital complication of acute and chronic sinusitis presented in ENT and Ophthalmology department, Government Medical College Calicut, Kerala from January 2013 to September 2014. The purpose of this study is to evaluate clinical and radiological presentation, outcome of treatment and postsurgical complications of diagnosed case of orbital complications of acute and chronic sinusitis. Methods: All the patients were subjected to thorough clinical examination, ophthalmological evaluation and radiological evaluation. Computerized tomography of paranasal sinuses both axial and coronal planes, MRI in selected cases, histopathology, fungal culture, a semistructured proforma are the study tools in this study. All the patients in this study received appropriate medical and surgical treatment and done a follow up evaluation at first month and at 3 months. Results: Preseptal cellulitis is the most common complication in our study. Fungal sinusitis due to uncontrolled diabetes mellitus is the most common condition causing orbital complication in our study. Conclusions: Strict diabetic control, appropriate surgical and medical management and a vigilant follow up resulted in good outcome.